PEMBANGUNAN KAWASAN PERBATASAN: EFEKTIVITAS PENGELOLAAN KAWASAN PERBATASAN LAUT DI KABUPATEN BINTAN - Ardi Putra; Rizky Octa Putri Charin; Khairi Rahmi (LPPM Universitas Abdurrab, 2024)
Bintan Regency is one of the districts included in the border development priority of 4 Lokpri sub-districts, there are still obstacles that affect the effectiveness of this policy. This research aims to analyze the effectiveness of border area management in Bintan Regency. The method used is a literature study by collecting and analyzing data from various sources. The results of the research show that from 2020-2024 the central government and regional governments have carried out development activities for community welfare, both for basic services and improving the community's economy. There are also major challenges faced by the border management section which is still under the coordination of the regional secretariat (Setda ) and do not yet have full authority in managing budgets and programs, limitations in decision making, complex coordination, limited human resources, and financial limitations.